Validitas dan praktikalitas lks fisika materi kalor dan teori kinetik gas bermuatan literasi baru untuk kelas XI SMA - Syarafina R; Fatni Mufit; asrizal A (PILLAR OF PHYSICS EDUCATION, 2020)
The 21st .Century demands that1human resources are responsive and alert to face competitionr. The 2013 revised 2017 curriculum is an effort to welcome 21st century life, aimed at developing critical thinking skills, creative, collaborating and communicating. However, the reality in the field of student literacy at school is still low and literacy activities in learning are not going well. The solution to overcome these problems is to develop worksheets to improve new literacy. The purpose of this study determines the validity and practicality of the use of physics worksheet.This type of research were conducted by Research and Development (R&D). The object of this research is the LKS physics of heat material and the kinetic theory of the gas which is limited to one class XI. The data source of this research is the validator team including the physics lecturer of FMIPA and the students of class XI MIPA 1 of SMAN 1 Nan Sabaris as student worksheet users. Data7collection instruments used were: validity sheets, practicality sheets.8Data analysis technique used is descriptive analysis of the validity and practicality of the product.4Based on data analysis, two research results were presented. First, the student worksheet is very valid with a validity value of 89,66. Second, the use of physics worksheets is very practical with practicality accordingoto students 89.77. So, it was concluded that the student worksheet physics of heat material and the kinetic theory of gas are valid and practical used in learning physics to improve the new literacy of class XI high school students.